Nutrient deficiency and physical inactivity in middle-aged adults with dynapenia and metabolic syndrome: results from a nationwide survey - Mijin Kim; Toshiro Kobori (Nutrition & Metabolism)
Abstract Background This study examined the associations between dynapenia, metabolic syndrome (MetS), nutrient intake, and physical activity. Methods We used data from a cross-sectional study that included middle-aged men and women (40–64 years old) who participated in the Korea National Health and Nutrition Examination Survey (KNHANES) between 2014 and 2017. Patients (n = 4700) were categorized into four groups based on diagnosis of dynapenia and MetS: dynapenic MetS (DM), dynapenia alone (D), MetS alone (M), and non-dynapenia and non-MetS (NDNM). Dynapenia was defined as the lowest tertile of the BMI-adjusted handgrip strength. MetS was defined as central obesity plus two or more of the following features: elevated fasting plasma glucose, blood pressure, or triglycerides, or reduced HDL cholesterol. Nutrient intake and physical activity were assessed via questionnaires. Results In women, the DM group had a significantly lower intake of all nutrients except for total energy and carbohydrates compared to the NDNM group. In a model adjusted for age, osteoarthritis, and total energy intake, the DM group showed higher odds ratios (ORs) for not practicing resistance training (men: OR (95% confidence intervals (CI)) = 1.64 (1.22–2.20); women: OR (95% CI) = 2.26 (1.59–3.21)) and for engaging in physical activities below 600 metabolic equivalents of tasks per week (men: OR (95% CI) = 1.36 (1.05–1.78); women: OR (95% CI) = 1.29 (1.02–1.63)) than the NDNM group. The women in the DM group had significantly higher OR for leisure-related moderate (OR (95% CI) = 2.00 (1.49–2.68)) and vigorous (OR (95% CI) = 1.76 (1.10–2.82)) physical inactivity than in the NDNM group. Conclusions This study showed that the combination of dynapenia and MetS was associated with poor nutrient intake in women and low physical activity in both sexes. These findings provide a foundation for developing intervention strategies to address dynapenia and MetS.